PELAKSANAAN PENEGAKAN HUKUM TINDAK PIDANA PENIPUAN MELALUI TELEPON DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - HANDY SANNY; Rika Lestari; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The phone can facilitate us to communicate remotely with others without having to meet with that person. However, with the rapid advancement of technology and the increasing human capabilities so timbulah crimes, one of which is the crime of fraud by telephone. Based on the authors obtained data from Pekanbaru City Police, from 2012 until 2013 many reports to Pekanbaru City Police against criminal fraud through this phone and have increased. The purpose of this study, namely; First, know the law enforcement against criminal fraud over the phone by Pekanbaru City Police. Second, determine the barriers to the implementation of law enforcement against criminal fraud over the phone in the jurisdiction in Pekanbaru City Police. Third, knowing the efforts made to overcome the obstacles in the implementation of law enforcement against criminal acts by telephone within the jurisdiction of the City Police Pekanbaru. This type of research is a juridical sociological research, because the author directly examine the problems occurred. This research was conducted in Pekanbaru City Police, while the population and the sample is a whole party related to the problems examined in this study, the data sources used, the primary data, secondary data and data tertiary data collection techniques in this study with interviews, literature study and observation. From the research, there are three main issues that can be inferred. First, law enforcement against criminal fraud over the phone by Pekanbaru City Police have not run properly. Second, internal factors that impede law enforcement against criminal fraud through this phone is the lack of experts and lack of tracking device. External factors that impede law enforcement against criminal fraud by telephone within the jurisdiction of the City Police Pekanbaru is the lack of evidence and the lack of evidence from witnesses. Third, Pekanbaru City Police officers to disseminate to the public on criminal fraud through this phone. Suggestions author, First, should improve the performance of Pekanbaru City Police in dealing with criminal fraud through this phone. Second, add a special team and a tracking device. Cooperation with third-party data providers in the use of that provider.